THE EFFICACY AND SAFETY OF TRANSCRANIAL MAGNETIC STIMULATION IN TREATMENT-RESISTANT BIPOLAR DEPRESSION - Zengin, Gulizar; Topak, Osman Zulkif; Atesci, Oyku; Atesci, Figen Culha (MEDICINSKA NAKLADA, 2022)
Backround: The aim of the current study is to investigate the efficacy and safety of Transcranial magnetic stimulation (TMS) treatment, a non-invasive brain stimulation technique, on depressive symptoms in treatment-resistant bipolar depression (TRBD). Subjects and methods: The study included 29 patients between the ages of 18-65, with bipolar disorder depressive episode according to DSM-5 and with the decision of non-response to treatment according to the Canadian Mood and Anxiety Treatment Network (CANMAT). Patients were divided into two groups double-blind-randomly, 20 sessions of TMS and 20 sessions of sham TMS were applied crossover. Hamilton Depression Rating Scale (HAM-D), Beck Depression Inventory (BDI), Young Mania Rating Scale (YMRS) and TMS Side Effect Questionnaire were applied to the patients before the treatment, at the 2nd week which is the crossover phase, and at the end of the treatment at 4th week. Results: In both groups, the severity of depression was decreased significantly according to HAM-D and BDI scores after the procedure. As well as active stimulation, some positive placebo effects were observed with sham stimulation. But the decreases seen in HAM-D and BDI scores and response to the treatment were higher during the weeks when the groups received active stimulation (respectively p=0.000, p=0.001, p=0.005). At the end of the study, according to HAM-D, 55.7\% of the patients showed response to the treatment, 24.13\% partial response. According to BDI, 41.37\% of the patients showed response to the treatment, and 31.03\% partial response. No associations were found between TMS response and sociodemographic - clinical features, or type of the disease (p>0.05). During the study, no serious adverse effects such as seizures or manic / hypomanic switches were observed. Conclusions: The results of our study showed that TMS treatment is an effective and safe treatment for patients with treatment-resistant bipolar depression.
Keywords: bipolar depression; treatment resistant; Transcranial magnetic stimulation